Extraction of Preisach model parameters for fluorite-structure ferroelectrics and antiferroelectrics - Wang, Zheng (Sci Rep, 2021)
Flourite-structure ferroelectrics (FEs) and antiferroelectrics (AFEs) such as HfO(2) and its variants have gained copious attention from the semiconductor community, because they enable complementary metal-oxide-semiconductor (CMOS)-compatible platforms for high-density, high-performance non-volatile and volatile memory technologies. While many individual experiments have been conducted to characterize and understand fluorite-structure FEs and AFEs, there has been little effort to aggregate the information needed to benchmark and provide insights into their properties. We present a fast and robust modeling framework that automatically fits the Preisach model to the experimental polarization ([Formula: see text] ) versus electric field ([Formula: see text] ) hysteresis characterizations of fluorite-structure FEs. The modifications to the original Preisach model allow the double hysteresis loops in fluorite-structure antiferroelectrics to be captured as well. By fitting the measured data reported in the literature, we observe that ferroelectric polarization and dielectric constant decrease as the coercive field rises in general.